Mental health stigma and internship nursing students' attitudes toward seeking professional psychological help: a cross-sectional study - Yasmin Mohamed Mohamed Abdelmonaem; Mahmood Ahmed Osman; Nashwa Ahmed Hussein Abdel Karim (BMC, 2024)
Abstract Background Self-stigma and negative attitudes toward mental illness have been identified as significant barriers that hinder individuals from seeking psychological assistance, leading to adverse consequences in their lives. Aim This study aimed to assess mental health stigma and internship nursing students' attitudes toward seeking professional help. Methods A cross-sectional design was conducted in the current study including a purposive sample of 228 participants of internship nursing students using a Socio-demographic data sheet, Self-Stigma of Seeking Help scale (SSOSH), and Attitude toward seeking professional psychological help scale (ATSPPH). The data acquisition period spanned from August to November 2022. Results This study revealed significant insights into the attitudes of internship nursing students toward seeking professional psychological help. Gender emerged as a notable factor, with males exhibiting higher levels of self-stigma compared to females (mean = 2.872). Attitudes towards seeking professional help varied significantly based on age, gender, residence, and marital status. Specifically, participants aged 23 years, females, rural residents, and married individuals demonstrated the highest Mean scores reflecting attitudes that lean more positively towards seeking help. Furthermore, a significant negative correlation (r = -0.372, p < 0.01) was observed between self-stigma and attitudes toward seeking professional help. Conclusion This study concluded that more than three-fifths of internship nursing students hadn't stigma towards seeking professional psychological help while the vast majority had a positive attitude towards seeking professional psychological help. However, the majority of students reported that financial barriers, specifically the high cost of therapy, prevent them from seeking psychological help. This highlights the need for more affordable mental health services for this population.